Česká klasifikace neziskových organizací: případ občanských sdružení - Bachmann, Pavel (Univerzita Pardubice, 2012)
Czech Classification of Non-profit Organizations (CCNO) was created in accordance with three principles: compliance with international standard ICNPO, compliance with Czech Classification of Economic Activities (CZ-NACE) and on the basis of the other currently used classifications of nonprofits. It is just the latter principle, which is questioned in the presented paper. These classifications were rather created through ad hoc approach reflecting the needs of owners of databases than the actual structure of non-profit organizations. Therefore, the article aims on verification of the current classification functionality and possibly on the design of some improvements. Research was conducted by content analysis of websites from non-profit organizations (n=494) randomly selected from a single comprehensive database of Czech civic associations. Research findings show that the classification CCNO does not correspond to the most common form of NPO organization – the civic associations. The paper includes recommendations on embracing new subcategories focusing on sport activities into CCNO classification and also develops a new classification structure designated solely to civic associations.
Czech classification of non-profit organizations: case of civic associations
Keywords: classification; non-profit organization; civic association; Czech Republic